POSISI NAṢ DALAM IJTIHAD ‘UMAR IBN KHAṬṬĀB - Fahmi Jawwas (State Institute of Islamic Studies (IAIN) Palu, 2013)
Abstract. This article discusses the position of the naṣ in the ijtihad of ‘Umar ibn Khaṭṭāb. ‘Umar is a companion of the Prophet who is known to have insight and intelligence. He is known by Muslims as the father of the mujtahid. Courage in ijtihad sometimes spawned debate among scholars. Some have even considered that aspect of ijtihad put the benefit greater than the naṣ. This is because the results of ijtihad impressed-for some people-contrary to what is contained in the passage, both the Qur'an and Sunnah. Is it true that ‘Umar ibn Khaṭṭāb rule out naṣ in ijtihad such allegations as scholars? While on the other hand, 'Umar was a man who got recognition by the Prophet over his intelligence in understanding the religion (Islam). This is what will be examined in this paper.Kata kunci: ijtihad, maslahat, naṣ, fiqh